2002
DOI: 10.1039/b109587k
|View full text |Cite
|
Sign up to set email alerts
|

A ceramic electrochemical microreactor for the methoxylation of methyl-2-furoate with direct mass spectrometry coupling

Abstract: A ceramic electrochemical reactor (CEM) devoted to electrosyntheses was developed. The CEM was constituted by the assembly of five structured ceramic layers. On one layer, platinum interdigitated band electrodes with a submillimetre interelectrode gap were screen-printed. The microreactor chamber was constituted by seven channels and its volume was less than 100 microL. After a sintering step at 850 degree C for 1 h, the CEM appeared as a solid and compact unit. The CEM was directly connected to the six port v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…The NMR spectra of carbamates were usually very broad and sometimes separated into two signals due to the existence of rotamers. Especially in cases where two diastereomers exist, the 13 C NMR spectra were complicated and a few signals were occasionally buried. These compounds were characterized as a mixture of diastereomers.…”
Section: General Remarksmentioning
confidence: 98%
“…The NMR spectra of carbamates were usually very broad and sometimes separated into two signals due to the existence of rotamers. Especially in cases where two diastereomers exist, the 13 C NMR spectra were complicated and a few signals were occasionally buried. These compounds were characterized as a mixture of diastereomers.…”
Section: General Remarksmentioning
confidence: 98%
“…Vojak et al created a ceramic microdischarge device with LTTC technology, housing a stable Ne-discharge in a cylindrical cavity of 140 lm diameter and 230 lm length at a voltage of 137 V. [63] For organic synthesis, a ceramic microreactor for the methoxylation of methyl-2-furoate has been demonstrated. [64] Finally, Wilcox et al demonstrated that the technology is mature by integrating a PEM (polymer electrolyte membrane) fuel cell design including methanol gas reforming. [65] They also entered the field of microfluidics, producing channel, valve, and pumping systems, that either worked magnetohydrodynamically or by piezo actuation.…”
Section: Meso-scaled Devices Based On Co-fired Ceramic Tape Technologymentioning
confidence: 99%
“…The anodic oxidation of furans in methanol using H 2 SO 4 as the supporting electrolyte was carried out, and the effect of the residence time was investigated by mass spectrometry analysis [13].…”
Section: Interdigitated Electrode Configurationmentioning
confidence: 99%